Co‐production in action: Navigating the research‐to‐implementation space in wildlife conservation through a Community of Practice - Sami Livingston; Ashley A. Dayer; Allyssa Zebrowski; Abby Sterling; Nolan Schillerstrom; Thomas Archibald; Willandia Chaves (Conservation Science and Practice)
Abstract Effective conservation practices require addressing the divide between research and implementation. Co‐production, which emphasizes collaboration and diverse knowledge exchange, is increasingly recognized as valuable in conservation to address this challenge, yet empirical insights remain limited. This case study explores using a Community of Practice (CoP) as an avenue for facilitating co‐production in shorebird conservation. Centering researchers and practitioners within implementation initiatives, we evaluate factors enabling a successful CoP and barriers hindering members' experiences. Capacity emerged as the predominant barrier, while the leading factors contributing to CoP success were having a dedicated space to support labor division, relationship building, and informal learning among CoP members. Leveraging our evaluation insights, we offer practical recommendations for structuring a CoP to optimize these benefits and advance the integration of CoPs and co‐production principles in conservation practice.